Effectivity of pharmaca therapy compared to surgery In open-angle glaucoma - Budihardjo Budihardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Two problems arising in determining an appropriate glaucoma therapy are when to treat and how to treat. Open-angle glaucoma is treated when damage to the optic nerve has been demonstrated in the form of progressive pathologic cupping and or characteristic visual field defects, or when pressure is elevated to an extent that is likely to cause damage to the optic nerve. On the other hand, the interrelationship between medical and surgical therapy (argon laser trabeculoplasty & drainage surgery) is complex. Initial treatment of primary open-angle glaucoma has commonly been medical, with surgery undertaken only if medical treatment fails or is not well tolerated. However, this assumption is currently under study; in some cases initial surgery may prove to be more beneficial. Hence, review article was made to prove how beneficial medical or surgical treatment is.Key words: Primary open-angle glaucoma - medical therapy - argon laser trabeculoplasty - drainage surgery